Structured Copper Mesh for Efficient Oil-Water Separation Processed by Picosecond Laser Combined With Chemical Treatment or Thermal Oxidation - Liang, Zihang; He, Wanying; Chu, Dongkai; Qu, Shuoshuo; Yao, Peng (Frontiers in Nanotechnology, 2021)
Water/oil separation has great practical significance, which can use to cope with the growing oily industrial sewage discharge or marine oil spills, avoiding water pollution. Smart artificial super-wettable materials used for water/oil separation have aroused enormous interest because of their advantages of energy-efficiency and applicability across a wide range of industrial processes. Herein, we report a highly efficient, simple method for water/oil separation using copper mesh processing by picosecond laser processing combined with chemical treatment or thermal oxidation. After laser processing, the copper mesh surfaces show superhydrophilicity and underwater superoleophobicity, which can be used to separate water from oil. While after laser and chemical treatment and laser treatment combined with thermal oxidation, the surfaces become superhydrophobic and underwater superoleophilic, which can separate oil from water. Moreover, these three kinds of super-wettability mesh show highly separation efficiency, achieving more than 99%. Furthermore, the as-prepared mesh can be used for various oil separation, such as edible oil, kerosene, diesel, and so on. Thus, this work will provide insights for controllable oil/water separation, will also be beneficial to the study of microfluidic device, and smart filter.